"Poppy" yeast. (28th September 2015) - Rinaldi, Teresa
Abstract : Synthetic biology holds great potential for biotechnology but could also be easily abused. The case of a genetically modified yeast to produce morphine highlights the dilemma of dual use research and the potential for abuse by criminals.